Enhanced anaerobic degradation of azo dyes by biofilms supported by novel functionalized carriers. (June 2023) - Wang, Guang-Yuan; Ding, Jie; He, Lei; Wu, Tong; Ding, Meng-Qi; Pang, Ji-Wei; Liu, Lu-Ming; Gao, Xin-Lei; Zhang, Lu-Yan; Ren, Nan-Qi; Yang, Shan-Shan
Graphical abstract: Highlights: A functionalized carrier could improve biofilm tolerance to high loading of RR2. Biofilms based on functionalized carriers enhanced RR2 decolorization efficiency. Functionalized carriers shaped and stimulated enrichment of keystone microbes. Functionalized carriers stimulated growth of biofilms and secretion of EPS. The concentration of RR2 influenced microbial diversity and richness. Abstract: Azo dyes are significant organic pollutants known for their adverse effects on humans and aquatic life. In this study, anthraquinone-2-sulfonate (AQS) immobilized on biochar (BC) was employed as a novel carrier in up-flow anaerobic fixed-bed reactors to induce specific biofilm formation and promote the biotransformation efficiency of azo dyes. Novel carrier–packed reactor 1 (R1) and BC-packed reactor 2 (R2) were used to treat red reactive 2 (RR2) under continuous operation for 175 days. The decolorization rates of R1 and R2 were 96–83% and 91–73%, respectively. The physicochemical characteristics and extracellular polymeric substances (EPS) of the biofilm revealed a more stable structure in R1. Furthermore, the microbial community in R1 interacted more closely with each other and contained more keystone genera. Overall, this study provides a feasible method for improving the biotransformation of azo dyes, thus providing support for practical applications in wastewater treatment projects.